2020
DOI: 10.1038/s42004-020-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

The proximity of aluminium atoms influences the reaction pathway of ethanol transformation over zeolite ZSM-5

Abstract: The organization of aluminium atoms in zeolites affects their catalytic properties. Here we demonstrate that the aluminium distribution is a key parameter controlling the reaction pathway of acid catalysed reactions over ZSM-5 zeolites. We study ethanol transformation over two ZSM-5 samples with similar Si/Al ratios of~15, and with aluminium atoms located mainly at the channel intersections but differently distributed in the framework. One of the samples contains mostly isolated aluminium atoms while the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…4 (c)). The occurrence of protonated ethanol dimers through ethanol dehydration on zeolitic catalysts was confirmed in previous reports [47][48][49].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 84%
See 1 more Smart Citation
“…4 (c)). The occurrence of protonated ethanol dimers through ethanol dehydration on zeolitic catalysts was confirmed in previous reports [47][48][49].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 84%
“…Based on experimental investigation, an ethanol sensing mechanism is proposed and schematized in Fig. 7, where steps (i) to (iv) are devoted to the adsorption process and steps (v) to (vii) including The formation of protonated ethanol dimers was confirmed in previous studies during ethanol dehydration on zeolite catalysts [48,60,61]. The ethoxy group can transform whereas acid sites are regenerated and as a result can provide ethylene [62,63].…”
Section: Sensing Mechanismmentioning
confidence: 81%
“…The polarization ability of anions together with OHon the N atom charge decreases in the order OH -> Cl -> PO4 3-> NO3 -: the lower the positive charge on the N atom, the lesser population of Al pairs and higher incorporation of single Al atoms sited in the vicinity of TPA + . Two ZSM-5 samples of similar Si/Al ratio (≈ 15) were prepared from dry amorphous aluminosilicate precursors with the assistance of TPAOH as OSDA [184]. Silica sol was employed as the Si source, and in the sample ZSM-5(p) Al source was aluminium butoxide while in the ZSM-5(s) polyaluminium chloride PAX-18 was used.…”
Section: Mfi-type Materialsmentioning
confidence: 99%
“…Besides, the adjacent Brønsted sites facilitate the dimerization and hydrogen-transfer reactions. The data suggest that the regeneration of Brønsted acid sites at higher temperatures takes place via releasing of ethane [184]. Another study reports the synthesis of two series of ZSM-5 zeolite materials with silica sol and tetraethylorthosilicate (TEOS) as the silicon source.…”
Section: Mfi-type Materialsmentioning
confidence: 99%
“…Besides, Sarve et al, reported that some of the ethylene molecules adsorbed on Lewis acid sites and metallic sites of the Al20-HAP80-Pd catalyst act as an intermediate for diethyl ether. According to the research works, ,, the dehydration of ethanol to diethyl ether is represented by two different pathways, termed the dissociative pathway and associative pathway (Scheme b). The dissociative pathway occurs by one ethanol molecule adsorbed on the catalyst and followed by water molecule elimination to obtain the adsorbed ethoxide.…”
Section: Resultsmentioning
confidence: 99%